(untitled) (Sociología y tecnociencia, 2024)
Surveillance studies and Science and Technology studies have made important empirical and conceptual proposals for the study of surveillance assemblies. Surveillance cameras have been proposed as a solution to crime problems in the world, and despite multiple studies that question their effectiveness, they continue to be central in the speeches of politicians when promoting security. Most of the studies on CCTV in Latin America and especially in Colombia, focus precisely on understanding or evaluating their effectiveness and analyzing the consequences for space and citizens. This article presents the trajectory of the security assembly in Medellín, emphasizing its trajectory and what Schneier calls the theater of surveillance. This article presents a case of such theater and presents evidence to exemplify it. The work is the result of a documentary research, both in archives and in the news media. The analysis of these documents made it possible to identify the instances in which the theater of surveillance is executed, while establishing discourses and technologies that support each other. It concludes with a reflection on the importance of understanding the technological trajectories of these systems in order to identify possible alternatives to the problem of security.